Jobs and Transitions Out of Poverty : A Literature Review - Inchauste, Gabriela (World Bank, Washington, DC, 2013)
This paper summarizes the existing literature on the links between labor and poverty reduction. The vast majority of studies find that more and better paid work is critical in lifting people out of poverty. Studies analyzing poverty dynamics and economic mobility find that improved returns to endowments, particularly the returns to human and physical capital, are critical for exiting poverty. Although non-labor incomes and demographic changes can help to lift the poor out of poverty, there is no substitute for providing an enabling environment that fosters better work and pay for the poor.